THE INFLUENCE OF CLEAN AND HEALTHY LIFESTYLE (PHBS) KNOWLEDGE ON PHBS ATTITUDES DURING THE COVID-19 PANDEMIC AND THE IMPLEMENTATION OF HEALTH PROTOCOLS IN KEC. MANGGALA MAKASSAR CITY - Nurhasmi, Nurhasmi; Harun, Herlinda Mahdania; Ansar, Asnaeni (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2023)
One of the risk factors that can affect public health problems is public hygiene. People in Manggala District are generally at risk of disease, especially Covid-19 infection. This situation must be prevented to reduce the adverse effects that can occur. This service aims to improve a healthy lifestyle, including the prevention of Covid-19 infection in the Manggala District. A total of 39 people attended this counseling. The counseling method used is by providing education about clean and healthy lifestyles (PHBS) and role-playing. This counseling is one of the recommended programs to encourage the formation of a healthy environment.